Ameliorative Role of Cerium Oxide Nanoparticles Against Fipronil Impact on Brain Function, Oxidative Stress, and Apoptotic Cascades in Albino Rats - Elshony, Norhan; Nassar, Atef M. K.; El-Sayed, Yasser S.; Samak, Dalia; Noreldin, Ahmed; Wasef, Lamiaa; Saleh, Hamida; Elewa, Yaser H. A.; Tawfeek, Shereen E.; Saati, Abdullah A.; Batiha, Gaber El-Saber; Tomczyk, Michał; et al. (Frontiers in Neuroscience, 2021)
Fipronil (FIP) is an N-phenylpyrazole insecticide that is used extensively in public health and agriculture against a wide range of pests. Exposure to FIP is linked to negative health outcomes in humans and animals including promoting neuronal cell injury, which results in apoptosis through the production of reactive oxygen species (ROS). Therefore, the purpose of the current study was to investigate the neuroprotective effects of cerium oxide nanoparticles (CeNPs) on neuronal dysfunction induced by FIP in albino rats. Male rats were randomly classified into four groups: control, FIP (5 mg/kg bwt), CeNPs (35 mg/kg bwt), and FIP + CeNPs (5 (FIP) + 35 (CeNPs) mg/kg bwt), which were treated orally once daily for 28 consecutive days. Brain antioxidant parameters, histopathology, and mRNA expression of genes related to brain function were evaluated. The results revealed oxidative damage to brain tissues in FIP-treated rats indicated by the elevated levels of malondialdehyde (MDA) and nitric oxide (NO) levels and reduced activities of antioxidant enzymes such as superoxide dismutase (SOD) and glutathione peroxidase (GPx). On the other hand, the FIP’s group that was treated with CeNPs showed decrease in MDA and NO levels and increase in SOD and GPx enzymes activity. Besides, FIP-treated rats showed decreased butyrylcholinesterase (BuChE) activity in comparison to the FIP + CeNPs group. Moreover, FIP caused up-regulation of the expression of neuron-specific enolase (NSE), caspase-3, and glial fibrillary acidic protein (GFAP) but down-regulation of B-cell lymphoma-2 (BCL-2) expression. But the FIP + CeNPs group significantly down-regulated the GFAP, NSE, and caspase-3 and up-regulated the gene expression of BCL-2. Additionally, the FIP-treated group of rats had clear degenerative lesions in brain tissue that was reversed to nearly normal cerebral architecture by the FIP + CeNPs treatment. Immunohistochemical examination of brain tissues of rats-treated with FIP showed abundant ionized calcium-binding adaptor molecule 1 (Iba-1) microglia and caspase-3 and apoptotic cells with nearly negative calbindin and synaptophysin reaction, which were countered by FIP + CeNPs treatment that revealed a critical decrease in caspase-3, Iba-1 reaction with a strong calbindin positive reaction in most of the Purkinje cells and strong synaptophysin reaction in the cerebrum and cerebellum tissues. Based on reported results herein, CeNPs treatment might counteract the neurotoxic effect of FIP pesticide via an antioxidant-mediated mechanism.